2017
DOI: 10.1016/j.ijpam.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Disc battery ingestion; a single event with different outcomes

Abstract: Foreign body (FB) ingestion is a common problem especially in children below the age of 5 years. This is fueled by their curiosity to explore their surroundings. The ingested foreign body finds its way out of the gastrointestinal tract without any serious consequences most of the time. On the other hand, disc battery ingestion has been reported to cause serious harm when ingested including death. We report two patients who had ingested disc batteries and their respective outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The association between age and FBI was statistically significant in our study, with the 1-3-year-old age group accounting for 47% (n=116) (p=0.00) of cases. This result agreed with a previous study done in 2017, which reported that age was one of the most influencing factors in FBI [13]. In our study, coin ingestion was the most common FBI type, representing 46.7% (n=111) of cases; 17.2% (n=40) of cases presented with battery ingestion, which was similar to studies done in Saudi Arabia in 2018 and 2023 [4,14].…”
Section: Discussionsupporting
confidence: 93%
“…The association between age and FBI was statistically significant in our study, with the 1-3-year-old age group accounting for 47% (n=116) (p=0.00) of cases. This result agreed with a previous study done in 2017, which reported that age was one of the most influencing factors in FBI [13]. In our study, coin ingestion was the most common FBI type, representing 46.7% (n=111) of cases; 17.2% (n=40) of cases presented with battery ingestion, which was similar to studies done in Saudi Arabia in 2018 and 2023 [4,14].…”
Section: Discussionsupporting
confidence: 93%
“…Some authors say that endoscopic intervention is important when the battery is in the oesophagus, but when there are no symptoms, the battery is in the stomach and should be treated in a more conservative way [ 13 ]. Most of the time, it is not clear how to treat tracheoesophageal fistula, and it can be controversial, especially in children [ 12 , 14 , 15 ]. It is possible to treat the patient without surgery and hope that the fistula will close on its own [ 15 ].…”
Section: Discussionmentioning
confidence: 99%